2013
DOI: 10.1111/ddg.12067
|View full text |Cite
|
Sign up to set email alerts
|

Depression is a frequent co‐morbidity in patients with acne inversa

Abstract: Patients with AI have a higher risk of developing depression. Physicians should be alert to the possible development of depression when treating patients with this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 43 publications
8
94
1
4
Order By: Relevance
“…It was further demonstrated that depression level is undoubtedly linked to HS clinical stage. Similar findings were presented by Matusiak et al [24] , with 21% of patients with HS having coexistence of depression [see also 25,26 ].…”
Section: Discussionsupporting
confidence: 86%
“…It was further demonstrated that depression level is undoubtedly linked to HS clinical stage. Similar findings were presented by Matusiak et al [24] , with 21% of patients with HS having coexistence of depression [see also 25,26 ].…”
Section: Discussionsupporting
confidence: 86%
“…The prevalence of depression is higher among people with HS compared to those with other dermatological conditions [14•, 2830]. In the Danish self-report study, 48% of the ambulatory cohort with HS reported current or former depression diagnosed by a psychiatrist [15• •].…”
Section: Hs and Depressionmentioning
confidence: 99%
“…Pro-inflammatory cytokines in HS may mediate depression [38]. A case-control study of 45 German study subjects with HS found that the presence of inflammatory markers (C-reactive protein) were associated with higher depression scores on the Hospital Anxiety and Depression Scale [28•]. The authors concluded that inflammation in HS could lead to depression onset [28•].…”
Section: Hs and Depressionmentioning
confidence: 99%
“…42,43 Impaired sexual health, interpersonal relationship problems, emotional burden, feelings of lack of control, and depression are all found in disproportionate rates in patients with HS. [44][45][46] This finding is not surprising given the private and embarrassing nature of this disease, which is characterized by painful, often malodorous eruptions of intimate body parts.…”
Section: Discussionmentioning
confidence: 94%